Comparison of Different Models forthe Remediation of Crude Oil Contaminated Clay and Swampy Soil Environment - Uku E.P.; Dumkhana B.B. (International Journal of Pollution: Prevention & Control, 2023)
This research was carried out to compare different mathematical models for the determination of best practice or method for remediation of crude oil contaminated clay and swampy soil environment. The results obtained were utilized to calculate the highest specific rates, the disassociation constant, and the kinetic values in terms of first- and second-order kinetics. The use of the Lineweaver Buck plot was taken into consideration for the different reactors, and the maximum specific rate of substrate degradation and disassociation constant were evaluated and determined for both the powdered forms of the moringa seed shell, yeast, and NPK (nitrogen, phosphorus, potassium) in the swampy soil (Moringa olefara), and the elephant grass, yeast, and NPK in the swampy soil (Pennisetum purpureum). According to the research, crude oil degraded more quickly in reactors that contained a mixture of yeast, NPK, and powdered swamp soil (Moringa oleifera) from moringa seeds.
Keywords: Moringa seed; clay soil; comparison; remediation; swampy soil